Orphan Care in Russia - Victoria Schmidt (Social Work and Society)
Current public opinion about the residential care system in contemporary Russia is extremely negative. A majority of Russians, both citizens and professionals, consider that family placement is the best arrangement for orphaned children. The year 2007 was announced as the Year of the Child in Russia. The majority of officials interpreted it as the year of de-institutionalization of the residential care system for children in Russia. De-institutionalization is mostly identified as reform focused on family placement instead of placement in institutions. Vladimir Fridlyanov, the executive director of the Ministry of Science and Education, announced in May, 2007 that the government is going to transfer 120,000 children from institutions into families every year from 2007 until 2010 and reduce the number of residential care institutions by one-third (Nesterova 2007). But the likelihood of family placement is small, with the exception of the adoption of infants without serious pathologies, and the attempts of precipitant de-institutionalization (when children's homes are closed and children are distributed among families) have failed (children were returned into children homes). According to the opinion of the Ministry, the key obstacle to effective de-institutionalization is the lack of professionals in adoption and foster care (Vazhdaeva 2006).